Florence Lydia Graham, 2020: Turkisms in South Slavonic Literature: Turkish Loanwords in Seventeenth- and Eighteenth-Century Bosnian and Bulgarian Franciscan Sources: Oxford: OUP. 409 pp. - Johnson, A. Jakob (Slavia Centralis, 2021)
Avtor predstavlja delo F. Lydie Graham: Turkisms in South Slavonic Literature: Turkish Loanwords in Seventeenth- and Eighteenth-Century Bosnian and Bulgarian Franciscan Sources (2020).
Keywords: Turkisms in South Slavonic Literature: Turkish Loanwords in 17th and 18th century Bosnian and Bulgarian Franciscan Sources; turcizmi; južnoslovanska književnost; bosanščina; bolgarščina